ChEVAR technique for emergent aneurysm repair - a retrospective case series - Veterano, Carlos (2023)
INTRODUCTION: Chimney EVAR (ChEVAR) for the treatment of complex abdominal aortic aneurysm (AAA) has been largely relegated for when fenestrated endografts are unavailable, especially due to durability concerns. However, the off-the-shelf nature of ChEVAR makes it a good option for emergent AAA repair. We report our institutional experience in ChEVAR in an urgent setting.METHODS: ChEVAR procedures were collected from 2019 to 2023 in a tertiary hospital, and a retrospective analysis was performed. This includes gathered information from electronic medical records, surgical reports and the picture archiving system. Descriptive statistics were applied. The main endpoints were technical success, 30-day and 1-year survival.RESULTS: Five patients were submitted to urgent aneurysm repair using the chEVAR technique. Average age was 73,4 years and all patients were male. Arterial hypertension was present in 100% patients and all patients were ASA 4. Indications for surgery were post EVAR type 1a endoleak with associated rupture or abdominal pain in two patients; symptomatic/contained rupture of pararenal AAA in two patients; and contained rupture of a thoracoabdominal aneurysm in one patient. A total of eight target vessels were catheterized: two patients required single-vessel chimney and the remainder two-vessel chimney. Target vessels were two superior mesenteric arteries and six renal arteries. Technical success rate was 100% and 30-day mortality was 0%. There were no major complications. Follow-up time is 20.2 months (4.7-38). Target vessel patency during the follow-up period was 87.5%. Three patients (60%) died due to non-aortic related pathologies, on average 18 months after surgery (4.7-38), with a 1-year survival of 80%.CONCLUSION: Our experience with ChEVAR for emergent AAA repair is satisfactory, with high technical success rates and low short-term mortality. Sac regression, low rates of target vessel occlusion and type 1a endoleaks reveal a favourable profile for aneurysm exclusion. ChEVAR is a viable option in emergent setting for patients unfit for open repair.